Creative Process in Creating the Creative Content of “Roro Choreographer” Through Social Media Platforms (Catharsis, 2022)
The phenomenon of social media in the era of digital society as a medium of artistic expression has its creative challenges. Digital society undergoes a process of social interaction and social-cultural groups of the digital society where there are also digital-based professions such as Youtube and Selebgram. Social control in digital society starts from the community itself, such as using passwords to secure accounts adapted from real people and stratification in the digital society. They are considered the highest party as they can prepare extensive and qualified information.Social media has created a new culture, namely the culture of sharing content by social media users. It makes content an essential aspect because we can see how culture is developing in social media or cyberspace through existing content. The content that is interesting and in great demand by social media users is the content that is entertaining and has aesthetic value, including dance moves, musical activities, fine arts, and drama. TikTok, Instagram, and Youtube social media users named Roro Choreographer with real name Septi Wahyu Setyaningsih Sugiyo or Septi Kurniawan. In addition to content creators, she is also a teacher at SMP 18 Semarang. Her contents contain dance moves, but they are more inclined to Indian movements. To date, the video has been viewed more than a thousand times. This study aims to discuss or examine the creative process, content, and social media platform she uses to increase artistic creativity in the Digital Age. The method used the descriptive qualitative research method to obtain data from the field by conducting in-depth observations and interviews. The study results show the following points: 1) the creative process is presented with inspiration and critical thinking stages, artistic exploration stage, and fantasy stage. Creativity generates activity, or the existence of activity indicates creativity; 2) creative content contains several functional aspects such as identity, conversation (interaction), sharing, being present (exist), relationship, reputation (status), and group; 3) social media such as TikTok, Youtube, Instagram are platforms that make Roro Choreographer content more viral and creative.